Prevalence, course, and predictors of emotional distress in pregnant and parenting adolescents. - Milan, Stephanie; Ickovics, Jeannette R; Kershaw, Trace; Lewis, Jessica; Meade, Christina; Ethier, Kathleen (Journal of consulting and clinical psychology, 2004)
This study examines trajectories and correlates of emotional distress symptoms in pregnant adolescents (n = 203) and nulliparous adolescents (n = 188) from economically disadvantaged communities over an 18-month period. For both groups, the prevalence of significant emotional distress exceeded expectation based on adolescent norms; however, the severity of symptoms did not differ between the 2 groups. Results from growth curve modeling revealed a significant decline in symptoms during the study period for both groups, but pregnant adolescents experienced a different pattern of decline. Also, certain interpersonal factors (e.g., history of physical maltreatment, partner support) appeared to play a more important role in the emotional well-being of pregnant and parenting adolescents relative to nulliparous adolescents. Implications for early identification and intervention are discussed.
Keywords: Adolescent; Depressive Disorder, Major; Female; Humans; Parenting; Pregnancy; Pregnancy in Adolescence; Prevalence; Prospective Studies